Dynamics of Etiolation Monitored by Seedling Morphology, Carotenoid Composition, Antioxidant Level, and Photoactivity of Protochlorophyllide in Arabidopsis thaliana - Jedynak, Pawel; Trzebuniak, Kamil Filip; Chowaniec, Magdalena; Zgłobicki, Piotr; Banaś, Agnieszka Katarzyna; Mysliwa-Kurdziel, Beata (Frontiers in Plant Science, 2022)
Although etiolated Arabidopsis thaliana seedlings are widely used as a model to study the deetiolation process, the etiolation itself at the molecular level still needs elucidation. Here, we monitored the etiolation dynamics for wild type A. thaliana seedlings and lutein-deficient (lut2) mutant between 2 and 12 days of their growth in the absence of light. We analysed the shape of the apex, the growth rate, the carotenoids and protochlorophyllide (Pchlide) accumulation, and the light-dependent protochlorophyllide oxidoreductase (LPOR) transcripts. Differences concerning the apical hook curvature and cotyledon opening among seedlings of the same age were observed, mostly after day six of the culture. We categorized the observed apex shapes and presented quantitatively how distribution among the categories changed during 12 days of seedling growth. The Pchlide654/Pchlide633 ratio, corresponding to the amount of the photoactive Pchlide, was highest in the youngest seedlings and decreased with their age. LPORA, LPORB and LPORC transcripts were detected in etiolated seedlings and their content decreased during seedling growth. Expression of SAG12 or SAG13 senescence markers, depletion in antioxidants and excess ion leakage were not observed during the etiolation. Lack of lutein in the lut2 mutant resulted in slow Pchlide accumulation and affected other xanthophyll composition.